Women and political change: Evidence from the Egyptian revolution - Nelly El Mallakh; Mathilde Maurel; Biagio Speciale (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
We analyze the effects of the 2011 Egyptian revolution on the relative labor market conditions of women and men using panel information from the Egypt Labor Market Panel Survey (ELMPS). We construct our measure of intensity of the revolution – the governorate-level number of martyrs, i.e. demonstrators who died during the protests - using unique information from the Statistical Database of the Egyptian Revolution. We find that the revolution has reduced the gender gap in labor force participation, employment, and probability of working in the private sector, and it has caused an increase in women's probability of working in the informal sector. The political change has affected mostly the relative labor market outcomes of women in households at the bottom of the pre-revolution income distribution. We link these findings to the literature showing how a relevant temporary shock to the labor division between women and men can have long run consequences on the role of women in society.Online Appendix :
Keywords: J16; J21; J22; J30; 330